EFFECTIVE LEARNING STRATEGIES THROUGH SINGING EDUCATION - Utaminingsih, Esty Setyo; Haryono, Slamet; Wuriningsih, FR.; Intania, Belita Yoan (Research and Development Journal of Education, 2024)
Implementation of learning to sing in elementary schools is not optimal. The teacher only focuses on developing singing knowledge, so students can only sing without understanding the values of the song. This research aims to find out how to teach singing in elementary schools. The research method used is a literature study. His literature study was conducted to strengthen each of the arguments described. To support this argument, data sources are needed from secondary data. Data collection techniques include collecting articles that are relevant to the research title. These articles come from journals, theses, and dissertations. The results showed that students in the low class had the perception that they could sing better than students in the high class. Singing is a means of expression and expresses emotions. The application of the direct method can be followed by guided practice, giving feedback on student skill mastery, and training at home. The benefits of singing are that students become more cheerful, and the class atmosphere is active and fun. Elementary school students have a good interest in singing.